Abordagem contextualizada e interdisciplinar nos capítulos de equilíbrio químico e eletroquímica em livros didáticos de química aprovados pelo PNLD/2008/2012/2015/2018 - Leite, Maycon Batista (2020)
The contextualization and interdisciplinarity in the teaching of chemistry imply the comprehension of social reality, through a critical-reflexive approach to the studied context, which circumscribes the very process of construction of scientific and technological knowledge as well as the appropriations and implications of this knowledge in the globalized world. The app are constitutive approaches of the epistemological action, inherent to the educational process, which result in the act of transposition from one context to another and to the internal structures of the learner, constituting knowledge. The Didactic Book is "the" didactic resource of greatest relevance in the teaching of chemistry in Brazil and the National Program of the Didactic Book, “Programa Nacional do Livro Didático (PNLD )”, presents as its main purpose to impose a minimum standard of quality to the didactic book offered in the Brazilian publishing market. This work was developed with the objective of investigating which are the concepts of interdisciplinary and contextualized approach that the authors of the chemistry didactic book, approved by the PNLD/2008/2012/2015/2018, present in the chapters of Chemical and Electrochemical Equilibrium of their respective works. And, also, to verify if the PNLD is promoting an inductive effect in the improvement of the quality of the chemistry didactic book, regarding the analyzed concepts. The research is eminently qualitative and documental, in which the documents analyzed were the 10 works of Chemistry approved in the respective PNLD, divided into 27 volumes. For that, we resorted to Bardin content analysis, which presents itself as an analytical method of supplementary information through new meanings "hidden" by a first reading of the text, concomitantly with the manipulation of messages to highlight the indicators that allow inference about a reality other than the immediate message. The method provided us with data that made it possible to create four categories of analysis from the perspective of contextualization and three categories from the perspective of interdisciplinarity. Those of contextualization were characterized from the different "context levels" presented, among which the one that came closest to the contextualized approach was the one that promoted greater approximation between school chemical knowledge and social reality, which went beyond the simple textual approach and the scientific description of daily life. The category that came closest to interdisciplinarity was the one that established the greatest degree of integration among the different disciplines, simultaneously to the capacity of relating interdisciplinary scientific knowledge to the understanding of contexts and problems inherent to social reality. The analysis revealed that six of the ten works analyzed presented contexts representative of contextualization as an approximation between chemical knowledge and social reality and only one of these six presented, simultaneously, conceptual integrations and contexts representative of interdisciplinarity as an understanding of problems inherent to social reality. Four works, the ones that did not get new approval in the last PNLDs, of 2015 and 2018, presented a reducing view of contextualization in their respective works. Nine of the ten works did not present a representative approach of interdisciplinarity as an understanding of contexts and problems inherent to social reality. In general, the didactic books are more focused on the scientific description of daily life as a perspective of contextualization and interdisciplinarity. The PNLD promoted an inductive effect in the improvement of the quality of chemistry idactic book, regarding the concepts analyzed in the chapters of Chemical and Electrochemical Equilibrium, in the movement that was configured in the ten years of the program. It is important to emphasize the dynamic "process" character of the work of the PNLD and of the authors and authors of the didactic book, which implies the continuity of the research that involves the analysis of the didactic book of Chemistry of the PNLD.